Kinetic parameters determination using optimization approach in integrated catalytic adsorption steam gasification for hydrogen production - Khan, Z. (Elsevier Ltd, 2015)
Abstract Integrated catalytic adsorption (ICA) gasification provides an efficient mean to produce hydrogen rich gas. This article presents the prospect of ICA steam gasification of palm kernel shell. The effect of temperature, steam to biomass ratio and adsorbent to biomass are investigated for H2, CO, CO2 and CH4 composition to determine kinetic parameters by minimizing the error between experimental and modelling results. Based on the evaluated kinetic parameters, the model predicts the product gas composition for the effect of temperature, steam to biomass ratio and adsorbent to biomass ratio. A significant fitting of model predicted values to the experimental results is achieved. Furthermore, it is also found that the water gas shift reaction is non-spontaneous and far away from the equilibrium at a temperature range of 600°C-675°C which may be due to strong CO2 adsorption reaction. © 2015 Hydrogen Energy Publications, LLC.